Clinical Significance of Negative Costimulatory Molecule PD-1/PD-L1 on Peripheral Blood Regulatory T Cell Levels among Patients with Pulmonary Tuberculosis - Chenchen Yang; Fanchao Dai; Rexiti Pulati; Yan Jiao; Qian Xu (Journal of Tropical Medicine)
Objective. This study aimed to investigate the expression and clinical significance of negative costimulatory molecules programmed death-1 (PD-1) and programmed death ligand 1 (PD-L1) on CD4+CD25+CD127low regulatory T cells (Tregs) in peripheral blood of patients with active pulmonary tuberculosis (TB). Methods. A total of 30 patients with active pulmonary TB and 20 healthy controls were enrolled. The proportions of peripheral blood CD4+CD25+CD127low Tregs and the expression of PD-1 and PD-L1 on CD4+CD25+CD127low Tregs were detected among active pulmonary TB patients using flow cytometry. The associations of proportions of CD4+CD25+CD127low Tregs with the demographic and clinical characteristics of active pulmonary TB patients were evaluated, and the correlation between PD-1/PD-L1 expression and proportions of peripheral blood CD4+CD25+CD127low Tregs was examined among patients with active pulmonary TB using Pearson correlation analysis. Results. Flow cytometry detected a significantly higher proportion of peripheral blood CD4+CD25+CD127low Tregs in the TB group than in the control group (9.14% ± 2.66% vs. 6.39% ± 1.73%; t = 4.067, P<0.001), and a higher proportion of peripheral blood CD4+CD25+CD127low Tregs among active pulmonary TB patients with a positive anti-M. tuberculosis antibody than in those with a negative antibody (Figure 2(a)); however, there were no gender, M. tuberculosis culture, tuberculin test, CT examination, or sputum smear test-specific proportions of CD4+CD25+CD127low Tregs among patients with active pulmonary TB. The PD-1 (6.13% ± 3.53% vs. 24.78% ± 7.73%, P<0.05) and PD-L1 levels (2.97% ± 2.00% vs. 9.23% ± 5.76%, P<0.05) were lower on peripheral blood CD4+CD25+CD127low Tregs among the TB group than in the control group. In addition, Pearson correlation analysis revealed a positive correlation between PD-1 and PD-L1 expression on peripheral blood CD4+CD25+CD127low Tregs among patients with active pulmonary TB (r = 0.435, P=0.016) and a negative correlation between the proportion of peripheral blood CD4+CD25+CD127low Tregs and PD-1 (r = ‒0.344, P=0.024) and PD-L1 expression among patients with active pulmonary TB (r = ‒0.310, P=0.043). Conclusion. The proportion of CD4+CD25+CD127low Tregs is higher in patients with active pulmonary TB than in healthy controls, and the negative costimulatory signal PD-1/PD-L1 expression is downregulated among active pulmonary TB patients. Our findings provide insights into the illustration of pathogenic mechanisms and immunotherapy of active pulmonary TB.